Communication profiles of a group of young children (0–5 years) with foetal alcohol spectrum disorders - Kritzinger, Alta M. (Aletta Margaretha) (University of Pretoria, 2013)
Dissertation (MCommunication Pathology)--University of Pretoria, 2011.